Evaluation of Gelatin as a Biostimulant Seed Treatment to Improve Plant Performance - Wilson, Hiromi T.; Amirkhani, Masoume; Taylor, Alan G. (Frontiers in Plant Science, 2018)
The effect of gelatin, used as a biostimulant, was investigated on plant growth in greenhouse studies. Biostimulants are materials that stimulate plant growth, and gelatin, an animal protein hydrolysate, is classified as one type of biostimulant. Gelatin has a unique amino acid composition with a high percentage of proline and hydroxyproline. In a series of experiments gelatin capsules (# 3 hard gelatin) containing 7.1 mg nitrogen each, were placed adjacent to seeds of different crop species, at sowing time in individual growing containers and several growth parameters were measured. Different types of hydrolyzed collagen, including granulated gelatin, gelatin hydrolysate, and amino acid mixtures simulating the composition of gelatin were compared on cucumber plant growth. In addition, amino acid mixtures without proline, hydroxyproline or applied in combination were investigated on cucumber growth. All capsule treatments significantly enhanced crop growth compared to the nontreated control. The treatment with two gelatin capsules placed adjacent to each seed increased shoot dry weight of cucumber, pepper, broccoli, tomato, arugula and field corn, by 138, 244, 50, 45, 41 and 18 percent, respectively. In an experiment with cucumber alone, there was a positive linear relationship between the number of gelatin capsules from 0 to 3 capsules on plant growth and plant nitrogen content. Cucumber growth and plant nitrogen content was greater from the hydrolyzed collagen treatment compared with the low molecular weight gelatin hydrolysate, a mixture of amino acids or urea and all treatments provided an equivalent amount of nitrogen. Proline and/or hydroxyproline were not responsible for the biostimulant effect. In summary, gelatin provided nitrogen that enhanced plant growth. Moreover, gelatin was an effective biostimulant as the plant growth and nitrogen content was greater from two gelatin capsules compared to amino acid mixture of the same proportion and amount as the gelatin.